Information & communication flows in priority areas of science and technology within the CARICOM region - Wiltshire, Winthrop W. ([CARIRI] [Port of Spain]GY, 1982)
Identifies the major problems being encountered with respect to scientific and technological information in the CARICOM region in priority areas of science and technology. Seeks to determine the degree of interaction among agencies and personnel in CARICOM countries involved with science and technology, as well as the identification of gaps in the information infrastructure.